Shelf life of chill stored pangasius (Pangasianodon hypophthalmus) fi sh fi llets: effect of vacuum and polyphosphate - Madhusudana Rao, B.; Narasimha Murthy, L.; Prasad, M. M. (Indian Journal of Fisheries, 2013)
Pangasianodon hypophthalmus, commonly known as pangasius is internationally marketed in the form of frozen fi llets. Value addition for domestic markets in the form of fi llets, fi ngers, cutlets and fi sh balls may be an alternative but the lack of proper cold chain facilities (-18 Â°C) in the domestic sector is an impediment to market these products. The present study was taken up to determine the shelf life of pangasius fi llets in chilled condition (